(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Extractions are a routinely/commonly used technique in orthodontics as a method of gaining space for correction of malocclusion. Any technique that facilitates teeth removal atraumatically and thus decreases the possibility of such a complication is welcome. The purpose of this study was to assess a patient's response to extractions during orthodontic therapy.A cross sectional study was conducted on 200 patients who underwent fixed appliance therapy who visited Saveetha dental college and hospital. Thus the population includes all patients under fixed appliance therapy above the age group of 18 years. A survey software was used to reduce sampling bias. Repeated answers or questions were avoided. All patients undergoing fixed orthodontic treatment were included in the study. Data collection was done using a self structured questionnaire consisting of 12 questions. Google forms were used to collect the data and circulate among the patients. Variables such as gender and age were also collected. Data was assessed based on these variables. The data was analysed using SPSS statistical software, descriptive and analytical statistics was done with Chi square test. After tabulation using MS Excel, the data was exported to IBM SPSS software [Version 19: IBM Corporation NY USA] for statistical analysis.Internal validity of the study was carried out by analysing all patients under fixed appliance therapy, external validity was homogenization and replication of the experiment.It was observed that patients between 10-30 years(66;66.1%) were more aware about the treatment time when compared to the age group between 30-40 years(n=42;38.9%)Pearson’s Chi square value=1.561; df=1; p-value:0.212 (p>0.05),statistically not significant)It was observed that people in the age group of 18-30 years(n=72;64.3%) were more aware about the benefits of extraction during an orthodontic therapy when compared to the patient’s of the age group 30-40years(n=40;35.7%).Pearson’s Chi square value=0.57; df=1; p-value:0.811 (p>0.05),statistically not significant).It was observed that it was more predominant in the age group between 18-30 years and pain(n=57;71.3%) being that common reason for avoidance of extraction.Pearson’s Chi square value=4.084; df=2; p-value:0.130 (p>0.05),statistically not significant) It was observed that female(n=60;55.6%) were more aware about the benefits of extraction during an orthodontic therapy when compared to males(n=48;44.4%).Pearson’s Chi square value=2.899; df=1; p-value:0.089 (p>0.05),statistically not significant).It was observed that female(n=63;56.3%) were more aware about treatment time when compared to males(n=49;43.8%). Pearsons Chi square value=3.977; df=1; p-value:0.046 (p<0.05),statistically significant) It was common in both the gender and Majority of the patient’s chose pain(n=40;50%) as their reason to avoid extraction. Pearsons Chi square value=0.533; df=2; p-value:0.766 (p>0.05),statistically not significant).Within the limitations of the study it was observed that females were more aware and positive about extractions during an orthodontic therapy when compared to males. It was more predominant in the age group between 18-30 years. It was also observed that the majority of the patients had pain as the reason for avoiding extraction if indicated during an orthodontic therapy.Awareness on extractions as a method space gaining and appropriate management might help in the attainment of ideal occlusion without the need for extensive orthodontic therapy